Evaluation of critical operations capabilities for competitive manufacturing in a high-cost environment. (24th July 2020) - Sansone, Cinzia; Hilletofth, Per; Eriksson, David
Abstract : Purpose: To survive in a competitive landscape, companies are required to identify, develop and continuously improve upon the operations capabilities that have the greatest impact on the overall competitiveness. This paper aims to evaluate critical operations capabilities for competitive manufacturing in a high-cost environment. Design/methodology/approach: Critical operations capabilities for competitive manufacturing were extracted in a literature review and then evaluated from the perspective of a high-cost environment in a focus group study. The focus group included a quantitative (questionnaire) and qualitative (discussion) evaluation of the extracted critical operations capabilities. Findings: The empirical findings revealed that all the capabilities identified in the literature review are considered critical in a high-cost environment, albeit with varying emphasis. Companies located in a high-cost environment tend to emphasize a broad set of capabilities related to quality, cost, time, flexibility and innovation rather than only cost-related capabilities. Research limitations/implications: The research is based on a focus group that was limited to 14 representatives from five Swedish manufacturing companies. This can reveal some limitations with regard to the generalizability of the conclusions drawn. Hence, this research should be considered as an initial step in gaining a more in-depth and complete understanding of the research topic under investigation. Practical implications: The research outcome enables managers to design their operations strategy more systematically and effectively, to be consistent with their targeted capabilities. The operations capabilities are important for both the company's competitiveness and its future direction. Originality/value: The paper presents an updated understanding of how companies achieved a competitive advantage in a specific manufacturing environment such as a high-cost context. It additionally provides an overview of what capabilities are developed for implementing successful operations strategies.